2013
DOI: 10.1021/tx4001682
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Seafood as an Important Dietary Source of Heterocyclic Amines by Chemometry and Chromatography–Mass Spectrometry

Abstract: Heterocyclic amines (HCAs), which are formed during the cooking of protein-rich foods, are potent mutagens and a risk factor for human cancers. Levels of HCAs have been extensively investigated in meat products but not in fish products. Here, we report levels of HCAs in fried salmon, tuna, hake, sardine, angler fish, cod, sole, swordfish, squid, and cuttlefish. The HCA levels of some of these foods have not been previously analyzed. We employed multivariate factor-analysis tools, including principal components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 39 publications
2
19
1
Order By: Relevance
“…PhIP is usually found at higher concentrations in such types of meat, and the concentrations found in the current study were in good agreement with those reported by previous studies 34, 42 . Nonetheless, in other high-protein foods, such as cooked chicken and fish (swordfish), PhIP was found in very high concentrations (>100 ng/g), especially in swordfish 43, 44 . The HCA levels in such foods are higher than those detected in the present study and these food products are typically defined as being extremely HCA contaminated 43, 44 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PhIP is usually found at higher concentrations in such types of meat, and the concentrations found in the current study were in good agreement with those reported by previous studies 34, 42 . Nonetheless, in other high-protein foods, such as cooked chicken and fish (swordfish), PhIP was found in very high concentrations (>100 ng/g), especially in swordfish 43, 44 . The HCA levels in such foods are higher than those detected in the present study and these food products are typically defined as being extremely HCA contaminated 43, 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, in other high-protein foods, such as cooked chicken and fish (swordfish), PhIP was found in very high concentrations (>100 ng/g), especially in swordfish 43, 44 . The HCA levels in such foods are higher than those detected in the present study and these food products are typically defined as being extremely HCA contaminated 43, 44 . In addition, PhIP could also be the main HCA in the human diet.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is proven with epidemiologic studies that various chemical compounds form as a result of cooking foods rich in protein, such as cooking meat and fish at high temperatures. All of these compounds are mutagenic and majority of them are also considered as carcinogenic . Among these chemical compounds, heterocyclic aromatic amines (HCAs) have an important place.…”
Section: Introductionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t HCAs are a toxicological substances and present at parts per billion levels in heattreated proteinaceous foods such as meat (Sugimura et al 2004), poultry (Skog and Solyakov 2002), fish (Khan et al 2013), and offal products (Khan el al. 2009a) which play an important role in the etiology of human cancer (Sugimura et al 2004;Skog and Solyakov 2002;Khan et al 2013;Khan el al.…”
Section: Introductionmentioning
confidence: 99%
“…2009a) which play an important role in the etiology of human cancer (Sugimura et al 2004;Skog and Solyakov 2002;Khan et al 2013;Khan el al. 2009a;Sugimura 2000;Alaejos et al 2008;Helmus et al 2013).…”
Section: Introductionmentioning
confidence: 99%